Thomas Baldwin, James Fowler and Ana de Medeiros, eds. Questions of Influence in Modern French Literature. New York: Palgrave Macmillan, 2013. xxvii + 223 pp. - Audra L Merfeld-Langston (Studies in 20th & 21st Century Literature, 2016)
Review of Thomas Baldwin, James Fowler and Ana de Medeiros, eds. Questions of Influence in Modern French Literature. New York: Palgrave Macmillan, 2013. xxvii + 223 pp.
Keywords: French literature; modern literature; influence